Painleve expansions and the Einstein equations: the two-summand case - Dancer, A; Wang, M (2003)
We investigate the existence of Painlevé-Kovalevskaya expansions for various reductions to ordinary differential equations of the Ricci-flat equations. We investigate links between such expansions and metrics of exceptional holonomy. © 2003 Elsevier Science B.V. All rights reserved.